Efecto rebaño: una sencilla manera de contrastar la hipótesis de expectativas racionales - Vélez, Juan Sebastian (Sociedad y Economía, 2008)
The paper reviews the core of the literature regarding the Hypothesis of Rational Expectations (HRE). Theories concerning rational ways of violating the HRE are then presented. A model with no regressors estimated by OLS is used to test for it. A survey was conducted over a sample of professionals whose jobs imply the forecast of economic variables. It shows evidence about the existence of behaviors that might interfere with the HRE